Dissolution behavior and in vitro evaluation of sputtered hydroxyapatite films subject to a low temperature hydrothermal treatment - Ozeki, K.; Aoki, H.; Fukui, Y. (Journal of Biomedical Materials Research Part A, 2006)
Hydroxyapatite (HA) was coated onto titanium substrates using radio frequency sputtering. Some of the as‐sputtered films were hydrothermally recrystallized at 110°C. In immersion tests, the as‐sputtered film completely dissolved after 2 days in a culture medium, whereas the thickness of hydrothermally treated films increased with an increase in immersion period, reaching a thickness of 127% after a period of 4 weeks. The proliferation and alkaline phosphatase (ALP) activity of MC3T3‐E1 osteoblast‐like cells on the as‐sputtered and hydrothermally treated films were investigated, and the cell morphology was also observed using scanning electron microscopy. The proliferation of MC3T3‐E1 cells on the as‐sputtered films was suppressed, whereas proliferation on the hydrothermally treated films was comparable to that on control and titanium substrate. The suppression of cell proliferation is associated with an increase in pH of the culture medium caused by dissolution of the as‐sputtered film. After a 96‐h culture time, the ALP activity of the cells on the hydrothermally treated film was higher than that on the control, titanium substrate, and as‐sputtered film samples. From scanning electron microscopic observations, it was found that the MC3T3‐E1 cells on the hydrothermally treated films were elongated and had established more intricate filopodia networks with each other, which were also observed for MC3T3‐E1 cells on the as‐sputtered films after a period of 24 h. © 2005 Wiley Periodicals, Inc. J Biomed Mater Res, 2006